Impacts of the Zero-Markup Drug Policy on Hospitalization Expenses of Patients with Stroke in Western China: An Interrupted Time Series Analysis - Wu Y; Han X; Qiu J (Dove Medical Press, 2024)
Yanghaotian Wu,1- 3 Xuemei Han,3 Jingfu Qiu1 1Department of Social Medicine and Health Service Management, School of Public Health, Chongqing Medical University, Chongqing, People's Republic of China; 2Department of Social Medicine, School of Public Health, Southwest Medical University, Luzhou, People's Republic of China; 3Institute of Social Medicine and Health Management, School of Public Health, Lanzhou University, Lanzhou, People's Republic of ChinaCorrespondence: Jingfu Qiu, School of Public Health, Chongqing Medical University, Yixueyuan Road, Yuzhong District, Chongqing, 400016, People's Republic of China, Email jfqiucqmu@163.comBackground: In 2016, an innovative medical pricing reform called zero-markup drug policy (ZMDP) was implemented in selected pilot cities in China, which focuses on curbing the unreasonable growth of medical expenses. This study aimed to evaluate the impacts of ZMDP on medical expenditure of stroke in western China.Methods: The quantitative data of inpatients diagnosed with stroke was extracted from the medical insurance system in 7 tertiary public hospitals. An interrupted time series (ITS) was used to analyze the instantaneous level and long-term trend changes of hospitalization expenses per visit from January 2015 to November 2018.Results: A total of 22,407 stroke inpatients were extracted. The total hospitalization expense per visit had the highest proportion of 20,000 CNY and above (33.66%). After the ZMDP, the median total hospitalization expense and western medicine expense per visit decreased by 631.74 CNY and 966.35 CNY, respectively (P < 0.001). Before the policy, the total hospitalization expense, traditional Chinese medicine (TCM) expense, examination expense, treatment expense, laboratory expense and surgical expense per visit showed upward trends (P< 0.05), while the anesthesia expense per visit showed a downward trend (P< 0.001). When the policy was implemented, the anesthesia expense per visit instantaneously increased by 91.70% (P< 0.001). After the policy, the total hospitalization expense, western medicine expense, TCM expense, treatment expense and surgical expense per visit changed from upward trends to downward trends (P< 0.05). The anesthesia expense per visit changed from a downward trend to an upward trend (P< 0.001), and the examination expense per visit maintained an upward trend (P=0.005).Conclusion: The economic burden of stroke inpatients decreased significantly with the implementation of the ZMDP, especially for the drug expenses. The medical service expenses increased significantly, reflecting the improvement in the value of medical staff's technical labor. However, the unexpected increase in the examination expenses was likely to be associated with the unreasonable medical compensation mechanism.Keywords: zero-markup drug policy, stroke, interrupted time series, hospitalization expenses, drug expenses